Synthesis and Antioxidant Activity of 5’-Methoxycurcumin: A Yellow Pigment from Curcuma xanthorrhiza† - Venkateswarlu, Somepalli; S. Ramachandra, Marellapudi; V. Subbaraju, Gottumukkala (Asian Journal of Chemistry, 2016)
5'-Methoxycurcumin (6) an unsymmetrically substituted curcuminoid from C. xanthorrhiza, was synthesized starting from syringaldehyde (4) and vanillin (5), in a single step. The spectral data of synthetic 6 are in good agreement with those of natural 6 and it showed potent antioxidant activity.